2021
DOI: 10.1101/2021.04.29.442000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Water Stress and Disruption of Mycorrhizae Induce Parallel Shifts in Phyllosphere Microbiome Composition

Abstract: Water and nutrient limitation are key stressors that affect plant health and ecosystem function. These environmental factors impact both soil- and root-associated microbial communities, and systemically alter plant physiology, but it is less clear how they affect aboveground plant-microbe interactions. Through experimental manipulations in the field and growth chamber, we examine the interacting effects of irrigation, soil fertility, and root mycorrhizal associations on bacterial and fungal communities of the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The microbiome of the leaf phyllosphere involves the communities of bacteria, fungi, and protists, which can be investigated efficiently by molecular ecologies, such as high-throughput sequencing and metagenomic analysis (Koskella, 2020;Rastogi et al, 2013;Su et al, 2022). Additionally, the linkage between leaf phyllosphere microbiome and food productivity in response to climate warming was influenced by fertilizer management, drought stress, crop variety, and study region (Bechtold et al, 2021;Debray et al, 2022). Thus, we should collect data on leaf phyllosphere microbiome under climate warming, different fertilization management, crop variety, drought stress, and other factors to develop effective productivity strategies for global warming in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microbiome of the leaf phyllosphere involves the communities of bacteria, fungi, and protists, which can be investigated efficiently by molecular ecologies, such as high-throughput sequencing and metagenomic analysis (Koskella, 2020;Rastogi et al, 2013;Su et al, 2022). Additionally, the linkage between leaf phyllosphere microbiome and food productivity in response to climate warming was influenced by fertilizer management, drought stress, crop variety, and study region (Bechtold et al, 2021;Debray et al, 2022). Thus, we should collect data on leaf phyllosphere microbiome under climate warming, different fertilization management, crop variety, drought stress, and other factors to develop effective productivity strategies for global warming in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Perreault and Laforest-Lapointe (2022) reported that plant-microbe interactions in the phyllosphere drive plant host adaptation to global warming. Therefore, the investigation of the phyllosphere microbiome will be essential for understanding how global warming shifts plant communities given that the phyllosphere microbiome might protect plant hosts from the threat of future climate change (Debray et al, 2022;Koskella, 2020). Until recently, empirical evidence for the impacts of climate warming on leaf phyllosphere-associated microbiomes is lacking.…”
Section: Core Ideasmentioning
confidence: 99%